Sex differences in the hepatotropic effects of antiulcer drugs and placenta cryoextract in an experimental rat liver injury model - Hladkykh Fedir V.; Koshurba Illia V.; Komorovsky Roman R.; Chyzh Mykola O.; Koshurba Yuri V.; Marchenko Mykhailo M. (Scripta Medica, 2023)
Background/Aim: Sex-related variances in drug metabolism provide a foundation for refining treatment protocols for prevalent conditions based on the patient's sex. Tailoring treatment strategies based on sex is particularly noteworthy among patients with comorbid illnesses due to the potential for drug interactions and the impact of concurrent diseases on clinical outcomes. Aim of this study was to assess the hepatotropic effects of antiulcer drugs (esomeprazole, clarithromycin and metronidazole - E/C/M) and placenta cryoextract (CEP) within a simulated model of tetrachloromethane (CCl4 )-induced hepatitis combined with underlying ethanol-induced liver cirrhosis (EILC), with a focus on the role of subjects' sex. Methods: Using 112 male and female rats, the research explored the effects of different sex hormone levels. Chronic EILC was induced by administering a 50.0 % CCl4 oil solution (8 mL/kg) twice a week, combined with a 5.0 % ethanol solution, over 45 days. Total protein (TP) levels and alkaline phosphatase (AP) activity were measured spectrophotometrically. Results: The research findings indicate that the onset of EILC and the administration of E/C/M resulted in a significantly greater 10.8 % (p = 0.03) reduction in TP levels among females compared to males, without altering hormonal status. Introducing CEP led to a noteworthy (p < 0.001) rise in TP levels, by 30.8 % in males and 33.9 % in females, in the context of EILC and E/C/M administration, while maintaining hormonal status. Among male rats, the most elevated AP activity was observed with excess testosterone propionate administration (5.0 [5.0; 5.9] mmol/L), while the lowest level was recorded in rats after testectomy, measuring 3.8 [2.5; 4.7] mmol/L, exhibiting a significant 20.8 % decrease (p < 0.05) compared to male rats without hormonal status changes. In female rats, the study revealed that against the backdrop of EILC and E/C/M administration, the highest AP level was seen in ovariectomised females, reaching 5.8 [5.1; 6.2] mmol/L, reflecting a substantial 9.4 % increase compared to rats without hormonal status changes. Conclusions: The administration of CEP under similar experimental conditions led to the recovery of the liver's protein-synthesising function in both male and female rats. When female sex hormones were introduced to sham-operated female rats, a significant 20.8 % greater reduction in AP levels was observed. Additionally, gonadectomy led to a more pronounced decrease in this enzyme's levels in male rats compared to female rats, indicating the cytoprotective properties of female sex hormones.